Tectonic Setting and Evolution of the Grenville Orogen: An Assessment of Progress Over the Last 40 Years - Rivers, Toby (Geoscience Canada, 2015)
The Grenville Province is known for its high grade of metamorphism, complex ductile gneissic structure, and polyphase reworking, features indicative of residence in the deep crust (orogenic infrastructure) that hamper recognition of protoliths and original relationships and render tectonic interpretations especially challenging. This paper charts the evolving understanding from the ‘Grenville Problem’ of the 1950s before the plate tectonic paradigm, through a speculative quasi-plate tectonic stage in the 1970s that effectively proved to be a dead end, and the first constrained plate tectonic models for pre-Grenvillian Laurentia in the 1980s, to the recent LHO (large hot orogen) and collapsed LHO models for the Grenville Orogen itself. The collapsed LHO model is based on the finding that significant amounts of the superstructure (upper orogenic crust) are preserved, and that the present crustal architecture can be explained by tectonic juxtaposition of infrastructure and superstructure in a late extensional event associated with crustal-scale collapse of a high-strain channel under an orogenic plateau. Conceptual breakthroughs and critical datasets assembled in the period 1980–2000 that were influential in guiding tectonic thinking are discussed and it is argued that present understanding was contingent on the results of 2-D numerical forward modelling of orogenesis, in particular the LHO experiments and the more recent models of orogenic collapse. As a result, for the first time a conceptual plate tectonic model for the convergence and collapse stages of the Grenville Orogen based on empirical field data (the inverse model) is broadly supported by numerical forward-modelling experiments constrained by physically plausible processes in a LHO – and both are available for future testing and refinement. Moreover, they may also have application to other enigmatic high-grade Proterozoic orogens that have resisted simple incorporation within the plate tectonic narrative. SOMMAIRE La Province de Grenville est bien connue pour le métamorphisme élevés de ses roches, leur structure ductile gneissique complexe de ses roches et leur remaniement polyphasé, caractéristiques qui correspondent à un séjour dans la croûte profonde (infrastructure orogénique) ce qui gène la reconnaissance des roches d’origine et leurs relations, et rendent particulièrement difficile les interprétations tectoniques. Le présent article retrace l’évolution de la compréhension du « problème du Grenville », à partir des années 1950, avant l’avènement du paradigme de la tectonique de plaques, en passant par l’étape d’une interprétation quasi- tectonique de plaques des années 1970, laquelle s’est avérée une impasse, puis par les premiers modèles balisés de tectonique de plaques de la Laurentie pré-grenvillienne des années 1980, jusqu’aux modèles récents des grands orogènes chauds (LHO) et de LHO d’effondrement visant à expliquer l’orogène de Grenville lui-même. Le modèle de LHO d’effondrement repose sur le fait que des portions importantes de la superstructure (croûte orogénique supérieure) sont préservées, et que l’actuelle architecture crustale peut s’expliquer par la juxtaposition tectonique de l’infrastructure et de la superstructure lors d’une phase d’extension tardive associée à un effondrement à l’échelle de la croûte d’un canal de fortes contraintes sous un plateau orogénique. Nous présentons ici les percées conceptuelles ainsi que les bases de données essentielles constituées de 1980 à 2000 qui ont orienté la réflexion tectonique, et nous proposons que la compréhension actuelle découle des résultats de la modélisation prospective numérique 2-D de l’orogenèse, en particulier des expériences LHO et des modèles plus récents d’effondrement orogénique. Et donc, pour la première fois, nous disposons d’un concept de modèle de tectonique de plaques permettant d’expliquer les phases de convergence et d’effondrement de l’orogène de Grenville qui découle de données empiriques de terrain (modèle inverse), et qui correspond largement aux résultats de modélisations prospectives numériques balisées conformes aux processus physiques d’un LHO, les deux étant disponibles pour essais et affinement. En outre, ils peuvent aussi être appliqués à d’autres orogènes protérozoïques de nature semblable et qui n’ont pu s’expliquer par la logique de plaques tectoniques.